Strong antibiotic resistance profiles in Salmonella spp. isolated from ground beef in Central Mexico - Campos Granados, Carlos Mario (2023)
We determined the prevalence of Salmonella enterica (SE) in retail ground beef sold across eight state capital cities from Central Mexico (n = 115) as well as the antimicrobial resistance (AMR) phenotype and genotype of the isolates obtained. SE was detected in 48/115 samples, with variable prevalence (10–80 %) across geographical regions (c2 = 24.2, P = 0.0021). We collected 116 isolates and observed circulation of serovars implicated in human salmonellosis in Mexico (Agona, Anatum, Infantis, Newport, Derby, Give y Typhimurium). Resistance was more frequently observed for tetracycline (39.7 %), chloramphenicol (37.9 %), streptomycin (37.1 %), trimetoprim-sulfamethoxazole (31.0 %), and ampicillin (28.4 %). Resistance against azithromycin was moderate (14.7 %), few isolates resisted cephalosporins (2.6-3.4 %), all were susceptible to carbapenems, and 38.8 % of the isolates were multidrug resistant (MDR). The sequenced genomes carried AMR alleles against aminoglycosides (aadA, aac, aph), beta-lactams (bla-CARB, bla-PSE, bla-TEM, bla-CTX-M, bla-CMY), phenicols (floR), folate pathway inhibitors (sul, dfrA), fluoroquinolones (qnrAB, oqxAB), tetracyclines (tetABM), and macrolides: mph(A) y lnu(F). In conclusion, the beef under study works as a reservoir of SE with worrisome MDR phenotypes. The pathogen has acquired AMR genes against antibiotics used in human and veterinary medicine. The emergence of resistance to azithromycin is particularly alarming and has not been reported to date. Further studies are needed to better characterize AMR in SE populations associated with cattle.